Resilience in Supply Chains: A Strategy Based on Inventory Policies - Eyssautier-Alvarado, Rodrigo; Marmolejo-Saucedo, José Antonio; García-Roa, Eduardo (Springer, 2024)
The resilience of supply chains is an increasingly important factor today. The effects of the COVID-19 pandemic have highlighted the importance of generating new strategies to reduce the risk of supply chain disruption. This paper proposes an inventory policy modeled in a simulation context. The case study is a hypothetical two-stage supply chain. The solution is given by the simulation of different scenarios where different data and policies are being taking into account to see different results and discard those policies that were not useful for this case study; all the simulations are made in anyLogistix software, which is a supply chain analytics software for designing and optimizing a supply chain. The results show the performance of the proposal in several disruption scenarios similar to those experienced in the COVID-19 pandemic. The solution proposal can serve as a reference in the functioning of supply chains in the post-COVID-19 era. ©Springer.
Keywords: Resilience in supply chains; Inventory policies